2007
DOI: 10.1152/ajpcell.00100.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of volatile and intravenous anesthetics on the activity of human TASK-1

Abstract: Volatile anesthetics have been shown to activate various two-pore (2P) domain K(+) (K(2P)) channels such as TASK-1 and TREK-1 (TWIK-related acid-sensitive K(+) channel), and mice deficient in these channels are resistant to halothane-induced anesthesia. Here, we investigated whether K(2P) channels were also potentially important targets of intravenous anesthetics. Whole cell patch-clamp techniques were used to determine the effects of the commonly used intravenous anesthetics etomidate and propofol on the acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 37 publications
3
54
0
Order By: Relevance
“…These changes in the electrocardiogram were not observed when the mice were treated with an intraperitoneal infusion of isoprenaline. In addition, we found that isoflurane, which activates TASK-1 channels [9,10], slows heart rate and atrioventricular conduction in wildtype mice, whereas these effects are not present in TASK-1 -/-mice. Taken together, our results suggest that TASK-1 may be important for the conduction of cardiac excitation and for the ventricular repolarization under resting conditions of the heart.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…These changes in the electrocardiogram were not observed when the mice were treated with an intraperitoneal infusion of isoprenaline. In addition, we found that isoflurane, which activates TASK-1 channels [9,10], slows heart rate and atrioventricular conduction in wildtype mice, whereas these effects are not present in TASK-1 -/-mice. Taken together, our results suggest that TASK-1 may be important for the conduction of cardiac excitation and for the ventricular repolarization under resting conditions of the heart.…”
Section: Introductionmentioning
confidence: 78%
“…Isoflurane exerts cardiac side effects via activation of TASK-1 channels, at concentrations which are in a clinically relevant range [9]. In previous work, general anesthesia with 1% isoflurane was found to reduce the heart rate of wildtype C57BL6 mice from 615 to 468 beats per minute (bpm) [22], whereas an anesthesia with Avertin ® did not bring about a reduction of heart rate [23].…”
Section: Isoflurane Modulates Heart Rate and Atrioventricular Conductmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, anandamide was reported to be highly specific for TASK-1 within the K 2P family (220). Based on this original report, anandamide and methanandamide were routinely used for the identification of TASK-1 in native tissues, glomus cells (95), smooth muscle cells of the pulmonary artery (123), cardiomyocytes (280), and cerebellar granule neurons (220). However, reexamination disproved the specificity; anandamide and methanandamide were found to inhibit TASK-1 and TASK-3 with comparable potency in different species (2, 21, 323).…”
Section: Anandamide and Methanandamide: Nonspecific Task Inhibitorsmentioning
confidence: 99%
“…interference of sleep or of Table 1 Crude overview of anaesthetic actions on the main putative candidate receptors/channels (red, strongly activating; orange, weakly activating; dark blue, strongly inhibiting; pale blue, weakly inhibiting; 0, no effect; n/a, data unavailable). Adapted from Rudolph and Antkowiak [19] using their broad definitions of strong/weak activation/ inhibition (with TASK results added from data of Putzke et al [20] and Pandit et al [21,22]. Results taken for sevoflurane and AMPA from [23], NMDA from [24] and HCN1 from [25].…”
Section: The Implications Of Anaesthesia's Being a Spectrum Of Brain mentioning
confidence: 99%